CTHRC1 overexpression predicts poor survival and enhances epithelial‐mesenchymal transition in colorectal cancer. (9th October 2018) - Ni, Shujuan; Ren, Fei; Xu, Midie; Tan, Cong; Weng, Weiwei; Huang, Zhaohui; Sheng, Weiqi; Huang, Dan
Abstract: Collagen triple helix repeat containing (CTHRC1), which was identified as a cancer‐related factor, is a promigratory protein involved in multiple processes, including vascular remodeling, antifibrosis, metabolism, bone formation, and cancer. In this study, we aimed to investigate the clinical significance and possible role of CTHRC1 in the process of epithelial‐mesenchymal transition (EMT) in colorectal cancer (CRC). Here, we revealed that CTHRC1 mRNA and protein levels are both upregulated in CRC tissues compared with those of paired noncancerous tissues. Moreover, the overexpression of CTHRC1 correlated with poor prognosis in patients with CRC (especially colon cancer). Furthermore, we showed that CTHRC1 induced EMT and promoted cell motility in CRC cells. Importantly, we demonstrated that CTHRC1 promoted EMT by activating transforming growth factor‐β (TGF‐β) signaling, revealing a possible effective therapeutic treatment for patients with CRC. Abstract : CTHRC1, epithelial‐mesenchymal transition, TGF‐β, colorectal cancer, prognosis.